Time preferences in decisions for others - Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
This paper analyzes in a within-subjects experiment time preferences when peopledecide for themselves and on behalf of others. The data show that subjects becomemore impatient when making decisions, which affect the payoff of others. Thechange can be explained by altruistic subjects who increase their focus on earlyconsumption when responsible for others' payoffs
Keywords: C91; D14; D15; D81; 330; Decisions fo rOthers; Experiment; Time Preferences